Cardiac epigenome in heart development and disease - Laurette, Patrick; Gilsbach, Ralf (Nature reviews. Cardiology, 2026)
Genetic and acquired forms of heart disease are leading causes of death worldwide. The epigenome, which governs cellular identity by modulating the accessibility of genetic regulatory elements, is established during development by transcription factors and has a pivotal role in the execution of cellular programmes. The epigenetic layers include DNA methylation, histone modifications and chromatin accessibility, which are dynamically regulated during development and in response to stress. Advances in single-cell and cell type-resolved epigenome analyses have provided unprecedented insights into the heterocellular nature of organs such as the heart, via the identification of epigenetic mechanisms and disease-associated epigenetic alterations in cardiomyocytes and other cardiac cell types. Chromatin remodelling, driven by specific modifiers, transcription factors and chaperones, orchestrates cardiac gene expression and contributes to disease manifestation and progression. Understanding how to modulate these epigenetic pathways in a cell type-specific manner offers promising avenues for therapeutic intervention, including epigenome editing for targeted modulation of regulatory elements. In this Review, we highlight studies decoding the various layers of the cardiac epigenome, emphasizing the interplay between cell type-specific mechanisms, describe emerging methods to study the cardiac epigenome, and discuss the translational potential of targeting epigenetic mechanisms for the prevention and treatment of cardiac diseases.
Gesehen am 11.02.2026